Mutation of the ALS-/FTD-Associated RNA-Binding Protein FUS Affects Axonal Development. - van Tartwijk, Francesca W.; Wunderlich, Lucia C.S.; Mela, Ioanna; Makarchuk, Stanislaw; Jakobs, Maximilian A.H.; Qamar, Seema; Franze, Kristian; Kaminski Schierle, Gabriele S.; St George-Hyslop, Peter H.; Lin, Julie Qiaojin; Holt, Christine E.; Kaminski, Clemens F. (Journal of Neuroscience, 2024)
Aberrant condensation and localization of the RNA-binding protein (RBP) fused in sarcoma (FUS) occur in variants of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Changes in RBP function are commonly associated with changes in axonal cytoskeletal organization and branching in neurodevelopmental disorders. Here, we asked whether branching defects also occur in vivo in a model of FUS-associated disease. We use two reported Xenopus models of ALS/FTD (of either sex), the ALS-associated mutant FUS(P525L) and a mimic of hypomethylated FUS, FUS(16R). Both mutants strongly reduced axonal complexity in vivo. We also observed an axon looping defect for FUS(P525L) in the target area, which presumably arises due to errors in stop cue signaling. To assess whether the loss of axon complexity also had a cue-independent component, we assessed axonal cytoskeletal integrity in vitro. Using a novel combination of fluorescence and atomic force microscopy, we found that mutant FUS reduced actin density in the growth cone, altering its mechanical properties. Therefore, FUS mutants may induce defects during early axonal development.
EVALuna2:595175